O uso da tecnologia de simulação na prática docente do ensino superior - Khalil, Renato Fares (2013)
Under the assumption that participation, integration and student engagement are fundamental to the learning process, this work present the research results that studied the use of simulation software in teaching practice. The research, a qualitative approach, was performed with higher education teachers and aimed to know what they think about the use of simulation software in the classroom. Among the theoretical foundations of the research are studies of Moran (2012) about technology as a pedagogical tool, also Pimenta and Anastasiou (2002), Pimenta and Ghedin (2002), which studied about higher education and teaching practice. For data collection Focus Group techniques were used, whose data were collected in meetings with the research¿ participants, focusing on the teachers¿ reflections about the possibilities and challenges of using simulation technologies in the learning process. The results indicated that the use of simulation as a pedagogical tool in the current context is quite positive and necessary, since it provides the teacher and the student look at reality from a different perspective. Also showed the possibilities and the difficulties of using this technology, mostly due to many teachers do not have training for the construction and use of the software in the classroom. This research allowed to understand that the use of simulation can contribute to build a dynamic class that can promote meaningful learning and motivate the student to construct new knowledge through reflection, research and collaboration. The conclusions signaled it is an innovative learning tool, and it is necessary the institutional support for training teachers so they can engage in these practices.